A Narrative Inquiry into EFL Teachers' Professional Experiences in Blended Learning during COVID-19 Pandemic - Ma'rufa, Ika Meilinda Ummul; Mustofa, Mutmainnah (International Journal of Language Teaching and Education, 2021)
Extensive studies have been geared to exploring the implementation of blended learning in education domain. However, there is a paucity of research that examines such implementation from teachers’ perspectives. To fill this gap, the present study investigates the lived experiences of EFL teachers in enacting blended learning during COVID-19 pandemic. To capture the teachers’ stories, a narrative inquiry was employed. Data were garnered through narrative frame, narrative box, and interview guide. Findings suggest that the teachers applied different online platforms to teach English in blended learning, then the school centralized to use Google classroom as the main platform in online class. Furthermore, the lesson, scheduling, Internet connection, and students’ self-regulated learning awareness complicated the implementation of blended learning during COVID-19 pandemic. The paper suggests policymakers to enact online pedagogy based on the actual teacher trainings and maximize schooling facility as a learning support.